Aligning Public Policy with REPowerEU Program Objectives by Adopting EESS Solutions: A Technology Acceptance Model Approach - Ion Popa; Marian Mihai Cioc; Stefan Catalin Pop; Daniel Botez; Marius-Ioan Pantea (Amfiteatru Economic, 2023)
The achievement of short-term energy savings through changes in user consumption behaviour is one of the main directions addressed by the REPowerEU program. This paper investigates the perspective of increasing energy efficiency at the level of domestic consumers in Romania by adopting energy efficiency smart solutions (EESS). The research is based on the extended technology adoption model and analyses the behaviour of Romanian consumers regarding the intention to use EESS solutions, in relation to three main influencing factors (awareness, environmental protection considerations, and public policy) moderated by demographic factors. To validate the research hypotheses, a survey was organised between January and March 2023, and structural equation modelling was used to highlight the effects of the determining factors on adoption intention. The research results suggest that all the predictors considered positively influence the behavioral intention to use EESS, with public policy having the greatest effect, followed by awareness. The results obtained suggest that the behaviour of household energy consumers towards adopting EESS is different depending on their age and average income. Additionally, through the IMPA model, a series of managerial interventions are formulated, mainly targeted at the authorities, in order to align Romanian public policies with the objectives of the REPowerEU program, in the context of promoting voluntary measures geared to the lifestyle and behaviour of household consumers by adopting EESS solutions. The limits of the research mainly refer to the lower familiarity acquired as a result of experience in use, in the context of the still early stage of development of the analysed technologies, but also to the exclusion from the analysis of some constructs of the extended model of technology acceptance, such as hedonic motivation or social influences, which would have allowed a more precise understanding of consumer attitudes.
Keywords: O33; Q48; Q58; 330; energy efficiency; public policies; the technology acceptance model; TAM; UTAUT; UTAUT2; smart devices; EESS